تقييم فعالية عملية تقييم أداء العاملين في المشافي العامة دراسة ميدانية على المشافي العامة في الساحل السوري - ميا علي; عبد الرحمن نسرين; عطية هنادي رمضان (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف هذا البحث إلى بيان مفهوم تقييم أداء العاملين وأهميته، بوصفه وسيلة هامة تمكن الإدارة من اتخاذ قرار موضوعي عن مستوى أداء الموظف وبيان مدى التحسن الذي تم تحقيقه على مستوى أدائه لواجباته ومسؤولياته، بالإضافة إلى معرفة مدى قدرته على تحمل مسؤوليات أعلى أو واجبات إضافية .وهذا ما يساعد في تحسين أداء العاملين وبالتالي تحسين أداء المشفى وزيادة فعالية أدائها، كما يهدف هذا البحث إلى بيان أهم العوامل المؤثرة في فعالية أداء المشافي العامة في الساحل السوري، واعتمد البحث المنهج الوصفي التحليلي واستخدم الاستبيان كأداة لجمع البيانات ثم تحليلها بواسطة البرنامج الإحصائي SPSS ، وقد توصل البحث إلى مجموعة من النتائج أهمها : ضعف خبرة القائمين بالتقييم بتقنيات التقييم وأساليبه وأبعاده، لا يحصل العاملون على التغذية العكسية اللازمة للوقوف على مستوى الأداء وتحسينه. تم اقتراح مجموعة من التوصيات أهمها: تدريب القائمين على عملية التقييم تدريباً كافياً حول تقنيات التقييم وأهدافه، تزويد العاملين بالتغذية العكسية اللازمة للوقوف على مستوى الأداء ، ضرورة تنوع نماذج التقييم تبعاً لتنوع وظائف المشفى. This research aims to examine the concept of Employees’ Performance Evaluation, as it is an important strategy that helps managers take an objective decision about the employee’s performance level. Also, it informs the extent of improvement that has occurred as related to the employees’ completion of tasks and their ability to bear high-level responsibilities and extra duties. Such appraisal will have a positive effect on achieving the objectives of the hospital and increasing its performance efficiency. This research studied the most important factors that affect performance efficiency in the public hospitals of the Syrian Coast. To conduct this research, questionnaires and descriptive, analytical, and statistical techniques were utilized to collect statistics. They were later analyzed by the statistical program SPSS. The findings of this research showed weak experience in evaluation methods and techniques. It was also surmised that no feedback was given to the employees. Such feedback should be required as it orients the employees with the level of their performance and makes the opportunity to improve possible. The recommendations of this research suggest that evaluators should undergo sufficient training in order to be oriented with evaluation concepts and techniques. Also, a suitable feedback about performance should be made available to the employees.